Revolutionizing Hospitality: Strategic Integration of Innovation Management Embracing Technological Innovation for Enhanced Customer Experiences - Giannoukou, Ioanna (Technium Business and Management, 2024)
This article critically examines the role of innovation in the hospitality sector, focusing on how hotels can enhance efficiency and customer satisfaction through digital advancements. It stresses the need for adapting to technological trends and consumer expectations. Also, it highlights the necessity for hotels to adapt to technological trends and evolving consumer expectations to maintain market relevance. The analysis highlights the integration of strategic planning, innovation management, cultural shifts, and technological adoption as key to fostering sustainable innovation. The importance of balancing traditional hospitality values with modern solutions to create competitive service offerings in the hotel industry is underscored. Key areas discussed include digital transformation in hotels, different tiers of innovation, and the challenges and strategies for implementing transformative innovations. The article concludes by emphasizing the necessity for hotels to combine operational efficiency, customer satisfaction, and game-changing innovation strategies, highlighting the potential of technologies like AI and robotics in revolutionizing the guest experience. It underscores the importance of balancing traditional hospitality values with modern technological solutions to create a unique and competitive service offering in the hotel industry.